2000
DOI: 10.3386/w7505
|View full text |Cite
|
Sign up to set email alerts
|

Two Generalizations of a Deposit-Refund System

Abstract: This paper suggests two generalizations of the deposit-refund idea. In the first, we apply the idea not just to solid waste materials, but to any waste from production or consumption -including wastes that may be solid, gaseous, or liquid. Using a simple general equilibrium model, we derive the optimal combination of a tax on a purchased commodity and subsidy to a "clean" activity (such as emission abatement, recycling, or disposal in a sanitary landfill). This "two-part instrument" is equivalent to a Pigovian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…13 The regulation we study here comprises an emission tax combined with an abatement subsidy, so we develop a model that takes into account the existence of an emission tax. We then show that similarly to the results in Fullerton and Wolverton (2000) and Fullerton and Mohr (2003), abatement subsidies can lead to increased emissions. We then show that similarly to the results in Fullerton and Wolverton (2000) and Fullerton and Mohr (2003), abatement subsidies can lead to increased emissions.…”
Section: Theoretical Modelsupporting
confidence: 65%
See 1 more Smart Citation
“…13 The regulation we study here comprises an emission tax combined with an abatement subsidy, so we develop a model that takes into account the existence of an emission tax. We then show that similarly to the results in Fullerton and Wolverton (2000) and Fullerton and Mohr (2003), abatement subsidies can lead to increased emissions. We then show that similarly to the results in Fullerton and Wolverton (2000) and Fullerton and Mohr (2003), abatement subsidies can lead to increased emissions.…”
Section: Theoretical Modelsupporting
confidence: 65%
“…In a general model, Fullerton and Wolverton (2000) and Fullerton and Mohr (2003) have shown that a subsidy to abatement increases emissions by lowering the cost of the polluting input, when there are no Pigouvian taxes. 13 The regulation we study here comprises an emission tax combined with an abatement subsidy, so we develop a model that takes into account the existence of an emission tax.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Metcalf and Weisbach (2009) discuss how regulated industries may treat upstream and downstream policies differentially. For example, if electric utilities face direct, end-of-pipe regulation and receive grandfathered permits, then regulators may limit their ability to pass 10 For perfectly competitive downstream markets, firms' first order condition imply w = p − k 0 − τ out r. The upstream monopolist maximizes profits by solving p + p 0 q − c 0 − k 0 − k 00 q = t in r + τ out r. Again, the policies are equivalent. Chiu et al (1998) reach the same conclusion for an upstream monopolist selling to downstream Cournot oligopolists.…”
Section: Regulationmentioning
confidence: 99%
“…This section looks at extremes of regulating only one vertical segment. However, some combination of upstream and downstream policies could provide incentives for lowering abatement costs but also keep transactions costs low (for example, seeFullerton and Wolverton (2000)). The discussion of offsets revisits this issue.…”
mentioning
confidence: 99%
“…Recently, Fullerton and Wolverton (2000) suggested the so-called deposit-refund system consisting of a tax on the consumption good (deposit) and a subsidy on recycling (refund) as a favorable alternative to the Pigouvian waste tax. In terms of our model the output tax and the recycled material subsidy at rates (25) take care of the deposit-refund system.…”
Section: Environmental Externalitymentioning
confidence: 99%